2000
DOI: 10.1046/j.1525-1373.2000.22339.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Fat Suppresses Protein-Induced Exocrine Pancreatic Secretion in Chronically Bile-Pancreatic Juice-Diverted Rats

Abstract: Previously, we showed that the increase in pancreatic enzyme secretion was lower after feeding a casein diet containing fat than that after feeding a fat-free casein diet in chronically bile-pancreatic juice (BPJ)-diverted rats. In the present study, we determined whether the suppressive effects of fats on flow volume of BPJ and pancreatic enzyme secretion depend on delaying gastric emptying and examined the characteristics of the suppression with intraduodenal instillation of soybean oil or lecithin in BPJ-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We also found that the sucrose esters stimulate release of PYY, which is known to inhibit pancreatic exocrine secretion. Although we previously reported that dietary fats (corn oil and soybean oil) suppress protein‐induced pancreatic secretion in PBD rats (Hara et al 1994, 2000), it had not been clarified whether the fat (triglyceride) itself or fatty acids and monoacylglycerol released by fat digestion in the ileal lumen triggered the inhibitory mechanism. To address this issue, we used sucrose fatty acid esters, from which free fatty acids are not liberated in the intestinal lumen because these compounds are resistant to digestive enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that the sucrose esters stimulate release of PYY, which is known to inhibit pancreatic exocrine secretion. Although we previously reported that dietary fats (corn oil and soybean oil) suppress protein‐induced pancreatic secretion in PBD rats (Hara et al 1994, 2000), it had not been clarified whether the fat (triglyceride) itself or fatty acids and monoacylglycerol released by fat digestion in the ileal lumen triggered the inhibitory mechanism. To address this issue, we used sucrose fatty acid esters, from which free fatty acids are not liberated in the intestinal lumen because these compounds are resistant to digestive enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…After a 24 h fast, cannulae were implanted into the common bile–pancreatic duct, duodenum and upper ileum under pentobarbitone anaesthesia (sodium pentobarbitone, 40 mg (kg body weight) −1 i.p. ; Abbott Co., North Chicago, IL, USA), as previously described (Hira et al 1997; Hara et al 2000). Briefly, the small tip (7–8 mm) of a polyethylene catheter (SP 28; i.d.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation